A Performance Aware Security Framework to Avoid Software Attacks on Internet of Things (IoT) Based Patient Monitoring System - Abinaya, E; Aishwarva, K; Lordwin, Cecil Prabhaker. M; Kamatchi, G; Malarvizhi, I (2018 International Conference on Current Trends Towards Converging Technologies (ICCTCT), 2018)
Internet of Things (IoT) is an established part of life by extending the communication and networking anytime, anywhere. IoT creates our lives simpler through a digital surroundings that will be perceptive, adaptive, and reactive to human desires. The Software attacks are the major sources of security vulnerabilities networks on a system. This type of attack consist of exploiting buffer overflows which is Denial of services, Trojan horse, worms and viruses intentionally insert malicious code into the system. The attack will be rectified by implementing the encryption algorithms such as Rivest-Shamir-Adleman (RSA) algorithm and Advanced Encryption Standard(AES) algorithms. These algorithms are implemented by using cryptool and the performances of loT devices are evaluated.